Tannin Analysis of Red Roselle Petals (Hibiscus Sabdariffa, L.) using Permanganometry Method - Anita Agustina Styawan; Aristhasari Putri; Refida Ramadhani Nur Cholifa (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Red roselle (Hibiscus sabdariffa L.) is a plant that can be used by the community as traditional medicine. Rosella flower petals contains protein, fat, minerals, alkaloids, flavonoids, and tannins. Red rosella is effective in preventing vertigo, antihypertension, antidiabetic, anticancer, and antioxidants. Tannins are known as one of the active ingredients contained in the petals of red rosella flowers. Tannins are polyphenolic protein. This study aims to determine the levels of tannin in the extract of red rosella flower petals using permanganometry titration. The research method used was observational. This study used a sample of red roselle flower petals. The sample was tested qualitatively using FeCl3 1%. Analyzed quantitatively using permanganometry titration. The results showed that qualitatively the positive sample contained tannins which was marked by a change in color to dark blue dark. Quantitatively the sample was titrated with KMnO4, the tannin content in red roselle flower petals was 13,73 % b/b.